2019
DOI: 10.1038/s41467-019-13194-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of genetic variants in the high-risk breast cancer susceptibility gene PALB2

Abstract: Heterozygous carriers of germ-line loss-of-function variants in the DNA repair gene PALB2 are at a highly increased lifetime risk for developing breast cancer. While truncating variants in PALB2 are known to increase cancer risk, the interpretation of missense variants of uncertain significance (VUS) is in its infancy. Here we describe the development of a relatively fast and easy cDNA-based system for the semi high-throughput functional analysis of 48 VUS in human PALB2. By assessing the ability of PALB2 VUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
113
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(132 citation statements)
references
References 52 publications
18
113
0
1
Order By: Relevance
“…Variant experimental analysis has led to in vitro treatments with specific agents that have been progressively introduced in the clinical practice. An example are the poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi), which were demonstrated to be effective in breast and ovarian cancers bearing mutations not only in BRCA1 and BRCA2, but also in genes involved in the DNA damage homologous recombination pathway, such as PALB2, RAD51, ATM, ATR and CHK2 [52,53]. The observation that also other "BRCAness" genes were involved in PARPi sensitivity opened the possibility of investigating other kinds of malignancies with dysfunction in the DNA damage response, where these genes are high-to-intermediate risk factors [54].…”
Section: Vus: Definition and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Variant experimental analysis has led to in vitro treatments with specific agents that have been progressively introduced in the clinical practice. An example are the poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi), which were demonstrated to be effective in breast and ovarian cancers bearing mutations not only in BRCA1 and BRCA2, but also in genes involved in the DNA damage homologous recombination pathway, such as PALB2, RAD51, ATM, ATR and CHK2 [52,53]. The observation that also other "BRCAness" genes were involved in PARPi sensitivity opened the possibility of investigating other kinds of malignancies with dysfunction in the DNA damage response, where these genes are high-to-intermediate risk factors [54].…”
Section: Vus: Definition and Consequencesmentioning
confidence: 99%
“…They range from homology-directed DNA repair assays [55,56], to in vitro transactivation of specific domains and measurements of ubiquitin ligase activity [57]. Studies with conditional knock-out cells allow to evaluate the capacities of HBOC-related gene variants to rescue lethality, DNA repair, and resistance to PARPi [48,53,58,59]. Other assays focus on micronucleus formation and centrosome amplification in mutated cell lines [60,61], on the restoration of resistance to damaging agents by BRCA2 re- introduction [60], or on increased chromosome breakage after γ-irradiation [62].…”
Section: Vus: Definition and Consequencesmentioning
confidence: 99%
“…Moreover, p.P8L (c.23C>T), p.K18R (c.53A>G), p.L24S (c.71T>C), p.Y28C (c.83A>G), and p.R37H (c.110G>A) compromise HR activity of PALB2 and are suggested to be pathogenic (106)(107)(108). In the PALB2 C-terminus, p.W912G, p.G937R, p.L939W, p.I944N (c.2831T>A), p.L947F (c.2841G>T), p.L947S (c.2840T>C), p.L961P, p.L972Q, p.A1025R, p.T1030I (c.3089C>T), p.I1037T, p.G1043D, p.L1070P (c.3209T>C), p.P1088S (c.3262C>T), p.W1140G (c.3418T>C), p.L1143P, and p.L1172P promoted a decrease in the HR activity of PALB2 (20,(107)(108)(109)112). Among these mutations, p.L939W, p.A1025R, p.T1030I, p.P1088S, and p.L1143P disrupt BRCA2-PALB2 interaction; p.W912G, p.G937R, p.I944N, p.L961P, p.L972Q, p.T1030I, p.I1037T, p.G1043D, and p.L1172P are associated with PALB2 protein instability; and p.I944N, p.L947F, p.L947S, p.T1030I, p.L1070P, and p.W1140G result in the mislocalization of PALB2 to the cytoplasm.…”
Section: The Challenges Of Palb2 Research In Clinical Applicationmentioning
confidence: 99%
“…A concurrent study conducted by Wiltshire et al revealed four new PARPi-hypersensitive variants in PALB2 (p.L24S, p.I944N, p.A1025R, and p.L1070P) using PALB2-deficient B400 mouse mammary tumor cells (108). Boonen et al(109) developed a cDNA-based system for the functional analysis of PALB2 variants. By evaluating the ability of PALB2 variants to rescue PARPi sensitivity in PALB2 knockout mouse embryonic stem cells, they identified twelve PALB2 variants (p.Y28C, p.L35P, p.W912G, p.G937R, p.I944N, p.L947S, p.L961P, p.L972Q, p.A1025R, p.T1030I, p.G1043D, and p.L1172P) that showed hypersensitivity to PARPi(109).In spite of the lack of clinical evidence for PARPi treatment efficacy in PALB2-deficient breast cancer patients, the response of some other PALB2-deficient solid tumors to PARPi in clinical/preclinical studies have been remarkable.…”
mentioning
confidence: 99%
See 1 more Smart Citation